Evaluation of Fire Protection System in Library Building Universitas Negeri Padang - Giatman, Muhammad; Kamil, Insannul; Kurniawati, Anugrah (CIVED, 2024)
The fire of a building will have a major impact on the building owner, both in the form of material, moral and environmental losses. In residential areas, offices and other public facilities often cause casualties. Therefore, a building needs to take into account the risk of fire so that building users can carry out activities safely and comfortably. One of the causes of fires is the fire suppression system that has not received full attention, where there is often an inadequate building fire protection system. The UNP Library Building is one of the public facilities buildings that are always crowded with students. It is necessary to evaluate the availability of the fire protection system to ensure the safety and comfort of its users. This research is in the form of an evaluation of the availability and completeness of the available fire protection systems and their remedies against the threat of fire. The data was taken through direct observation and question and answer and the distribution of questionnaires with the library. From the results of the analysis of the fire protection system inspection of the UNP Library building, it is known that on the 1st floor the lowest rediness value is 18.9%, for the 2nd and 3rd floors is 44.1%, the 4th and 5th floors are 45.9% and 45.6 % fulfilled the requirements based on the Minister of Public Works Regulation No. 26/PRT/M/2008.